Kemampuan Komunikasi Dasar Bahasa Inggris (Basic English) Program Studi Gizi Klinik, Politeknik Negeri Jember - Agus Setia Budi; Cholimatus Zuhro (Jurnal Yudistira : Publikasi Riset Ilmu Pendidikan dan Bahasa, 2025)
This study examined the Basic English ommunication skills of the Students of Clinical Nutrition Study Program at Politeknik Negeri Jember, especially in the first semester of the 2024/2025 academic year who are taking the Basic English Class. Using a quantitative and descriptive research approach, data was collected through tests designed to assess students' knowledge of English expressions used in everyday life. The test consists of 71 questions covering four topics. The test results showed good scores with most of the scores were categorized good and very good. Beside that, the difficulty index for each part of the test showed that students can answer the questions of the test that were categorized easy and very easy. The results of this study showed that students have good Basic English communication skills to prepare the students in entering the workplace in globalization era.